A direct, sensitive and high-throughput genus and species-specific molecular assay for large-scale malaria screening - Yaling Zhao; Ye Zhao; Yu Sun; Lihua Fan; Duoquan Wang; Heng Wang; Xiaodong Sun; Zhi Zheng (BMC, 2022)
Abstract Background Infectious disease diagnostics often requires sensitive molecular assays that identify at both genus and species levels. For large scale screening, such as malaria screening for elimination, diagnostic assay can be a challenge, as both the throughput and cost of the assay must be considered. The requirement of nucleic acid extraction hampers the throughput of most molecular assays. Co-amplification of multiple species or multiplex identification either can result in missed diagnosis or are too costly for large-scale screening. A genus- and species-specific diagnostic assay with simplified procedure, high sensitivity and throughput is still needed. This study aimed to develop a sensitive and high-throughput approach for large-scale infectious disease screening. Methods We developed multi-section Capture and Ligation Probe PCR (mCLIP-PCR) for the direct detection of RNA without extraction and reverse transcription. Multiple tailed sandwich hybridization probes were used to bind at genus- and species-specific sections of the target RNA to cooperatively capture the target onto a 96-well plate. After enzymatic ligation of the bound probes, a single-stranded DNA formed at each section with distinct tail sequence at the ends. They were separately PCR-amplified with primers corresponding to tail sequences for genus or species identification. We applied the method to the active screening of Plasmodium infections of 4,580 asymptomatic dried blood spot samples collected in malaria endemic areas and compared the results with standard qPCR using linear regression. Results With multi-section cooperative capture but separate amplification strategy, we accurately identified genus Plasmodium and species P. falciparum and P. vivax without RNA extraction, with favorable sensitivities among the published reports. In the active screening, our method identified all 53 positive infections including two mixed infections, and two P. vivax infections that were missed by standard qPCR. Conclusions mCLIP-PCR provides a sensitive and high-throughput approach to large-scale infectious disease screening with low cost and labor, making it a valuable tool for malaria elimination in endemic region. Graphical Abstract